Living with cancer : a practical guide - Visel, Dave, 1938- (Rutgers University Press, 2006)
In this essential guide, Dave Visel draws on expertise hard-won during his wife's battle with lymphoma. He provides an overview of the varieties of cancer and all the basic types of treatments available. Chapters dispel common myths associated with these treatments and provide tips on nutrition and physical fitness. Visel also moves beyond the hospital to provide information and strategies to help with the emotional, practical, and financial effects of a diagnosis. Cancer patients will find the tools they need to make well-informed decisions on questions ranging from the right time to tell cow.